Clinical, functional and prognostic correlates of blunted heart rate reserve during exercise stress echocardiography in hypertrophic cardiomyopathy. (8th February 2021) - Palinkas, ED; Varga, A; Agoston, G; Palinkas, A; Sepp, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Blunted heart rate reserve (HRR) during exercise is associated with cardiac autonomic dysfunction and poor outcome. Purpose: To evaluate the anatomical, functional and prognostic correlates of HRR during exercise stress echocardiography (ESE) in hypertrophic cardiomyopathy (HCM). Methods: We prospectively recruited a consecutive sample of 121 HCM patients [age 47 ± 13 years, 67 males; NYHA class 1.7 ± 0.7; left ventricular (LV) ejection fraction 71 ± 9 %; LV maximal wall thickness 24 ± 5 mm; 58 (48%) with LV outflow tract obstruction (LVOTO, gradient ≥ 50 mmHg) at rest] who underwent semi-supine bicycle ESE from January 2006 to September 2019. HRR was calculated as the peak/rest heart rate (HR) ratio. All patients were followed-up for a median of 7.5 years. Results: HR was 68 ± 11 bpm at rest and 105 ± 19 bpm at peak stress. Receiver-operating characteristic analysis was used to determine the best cut-off value of HRR (≤ 1.48, blunted) to predict all-cause death. A blunted HRR was present in 52 patients (43 %, Group 1). Patients with blunted HRR had more frequently hypertension (Group 1= 41/52 vs Group 2= 40/69, 79 vs 58 %, p = 0.019), resting systolic anterior motion of the mitral valve [(SAM), Group 1= 41/52 vs Group 2= 40/69, 79 vs 58 %, p = 0.019] and rest LVOTO (Group 1= 31/52 vs Group 2= 27/69, 60 vs 39 %, p = 0.029). Patients in Group 1 had larger left atrial diameter (48.8 ± 6.5 vs 46.5 ± 7.6, p = 0.076), lower LV end-diastolic [(EDD), 44.8 ± 4.6 vs 46.7 ± 4.6 mm p = 0.02] and LV end-systolic diameter [(ESD), 25.2 ± 5.3 vs 27.6 ± 5.5 mm p = 0.02] at rest. Patients in Group 1 had higher NYHA class (1.9 ± 0.6 vs 1.6 ± 0.7, p = 0.009), resting HR (71.5 ± 11.4 vs 64.6 ± 10.6 bpm p < 0.001), and shorter total exercise time (6.3 ± 3.1 vs 9.1 ± 2.8 min, p < 0.001) compared to patients in Group 2. During the follow-up, 13 patients died. All-cause death was observed in 10/52 patients of Group 1 and 3/69 patients of Group 2 (19 vs 4 %, p < 0.05). Cox multivariate regression survival analysis revealed that HRR ≤ 1.48 (Hazard ratio 3.7, 95% CI 0.96-14.5, p = 0.048) and left atrial diameter (Hazard ratio 1.15, 95% CI 1.04-1.28, p = 0.003) were independent predictors of all-cause mortality, either on or off beta-blocker therapy. Conclusion: HRR is a simple non-imaging biomarker of cardiac autonomic function and is frequently abnormal in HCM. The blunted increase in frequency is associated with NYHA functional class, exercise time, rest HR, rest LVOTO, SAM, LV EDD and ESD. HRR independently predicts survival in HCM. The lower the HRR, the worse the outcome.